KEPENTINGAN INDONESIA MENANDATANGANI BILATERAL INVESTMENT TREATY DENGAN SINGAPURA 2018 - Ronaldo David Ginola; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to explain Indonesia's interest in re-signing the Bilateral Investment Treaty (BIT) with Singapore on 11 October 2018, the Investment Agreement between Indonesia and Singapore, which began in 1990 and was renewed in 2005, was terminated in 2016 after the Indonesian government revised BIT in 2013.This study uses a Qualitative method to describe the reality of the properties and relation of the object under study,and the perspective of interdependent liberalism in which interdependent liberalism argues that the highest level of international relations is reciprocal dependence between countries. This study also uses the Interdependence theory with the level of nation state analysis.This study shows the governments of Indonesia and Singapore have previously collaborated in the development of the Kendal Industrial Zone which was successful in adding to the value of Indonesia's investment realization, Indonesia also offers 3 industrial estates to develop with Singapore which are expected to succeed such as the Kendal Industrial Park, besides that Indonesia also intends to increase its ranking The EODB (Ease of Doing Business) issued by the World Bank is the main reason Indonesia signed the BIT with Singapore.Keywords :  Bilateral Investment Treaty (BIT), Investment Industrial Estates, Singapore